“A Lynching in Blackface”: The Representation of History and Fantasies of Black Male Violence in John E. Wideman’s The Lynchers - Dexl, Carmen (Current Objectives of Postgraduate American Studies, 2012)
John Edgar Wideman’s novel The Lynchers “(1973) dramatizes African American plans to lynch a white policeman and thus promote the constitution of a black nation. Drawing on Linda Hutcheon’s intertextual conception of parody as elaborated in A Theory of Parody “(1985), this article examines the inversion of the lynching narrative at the core of The Lynchers“ as a “repetition with a critical difference“ (32). It argues that the novel’s adoption of parody serves three major functions: First, it exposes the specific workings of lynching. Second, it debunks central ingredients of the lynching mythology and third, it expresses a critical position towards the premises and implications of gendered black nationalism.